Pengaruh Antara Rasio Kecukupan Modal (CAR), Loan To Deposit Ratio (LDR), dan Rasio Biaya Operasional Pendapatan Operasional (BOPO) terhadap Kinerja Profitabilitas Industri Perbankan - budi zulfahri (Program Studi Manajemen Fakultas Ekonomi Universitas Samudra, 2017)
The influence between Capital Adequancy Radio (CAR), Loan to Deposit Ratio (LDR), Operating Cost To Operating Income Ratio on Profitability Performance of Banking Industry. Contribution of banking is very important to encourage economic development especially to increase industry. The important of contribution of bank to economic growth make many parties more concern about profitability performance of banking. Because of that objectives of the research are to know how the influence some of financial ratio which is represented by Capital Adequancy Ratio (CAR), Loan to Deposit Ratio (LDR), Operating Cost To Oprating Income Ratio on Profitability Performance that proxy by WA. The banking population in this research using all of general banking in Indonesia in 2008 amont 123 banking. This research using purposive sampling method to choose “My sample and based on the criteria, has known that 65 banks in Indonesia have a good financial ratio. The research used multiple regression analysis that have been access in normality test and assumption classic test. Based on the results of data hypothesis shoes that LDR has significantly and positively relation on ROA but BOPO has significantly and negatively relation on ROA. Whereas CAR has no significantly on ROA. The contribution of CAR, LDR, and, BOPO influenceses are 69,6% and the remained is influenced by the other factors which is no described.